The Interplay of Human and Mycobacterium Tuberculosis Genomic Variability - Correa-Macedo, Wilian; Cambri, Geison; Schurr, Erwin (Frontiers in Genetics, 2019)
Tuberculosis (TB), caused by the human pathogens Mycobacterium tuberculosis (Mtb) and Mycobacterium africanum, has plagued humanity for millennia and remains the deadliest infectious disease in the modern world. Mycobacterium tuberculosis and M. africanum can be subdivided phylogenetically into seven lineages exhibiting a low but significant degree of genomic diversity and preferential geographic distributions. Human genetic variability impacts all stages of TB pathogenesis ranging from susceptibility to infection with Mtb, progression of infection to disease, and the development of distinct clinical subtypes. The genetic study of severe childhood TB identified strong inborn single-gene errors revealing crucial pathways of vulnerability to TB. However, the identification of major TB-susceptibility genes on the population level has remained elusive. In particular, the replication of findings from candidate and genome-wide association studies across distinct human populations has proven difficult, thus hampering the characterization of reliable host molecular markers of susceptibility. Among the possible confounding factors of genetic association studies is Mtb genomic variability, which generally was not taken into account by human genetic studies. In support of this possibility, Mtb lineage was found to be a contributing factor to clinical presentation of TB and epidemiological spread of Mtb in exposed populations. The confluence of pathogen and human host genetic variability to TB pathogenesis led to the consideration of a possible coadaptation of Mtb strains and their human hosts, which should reveal itself in significant interaction effects between Mtb strain and TB-susceptibility/resistance alleles. Here, we present some of the most consistent findings of genetic susceptibility factors in human TB and review studies that point to genome-to-genome interaction between humans and Mtb lineages. The limited results available so far suggest that analyses considering joint human–Mtb genomic variability may provide improved power for the discovery of pathogenic drivers of the ongoing TB epidemic.